Trends in funding, internationalization, and types of study for original articles published in five implant-related journals between 2005 and 2009 - Barão, Valentim Adelino Ricardo [UNESP]; Shyamsunder, Nodesh; Yuan, Judy Chia-Chun; Knoernschild, Kent L.; Assunção, Wirley Gonçalves [UNESP]; Sukotjo, Cortino (My University, 2012)
Purpose: The aims of this study were to evaluate the trends in funding, geographic origin, and study types of original articles in the dental implant literature and to investigate the relationships among these factors. Materials and Methods: Articles published in Clinical Oral Implants Research, The International Journal of Oral & Maxillofacial Implants, Clinical Implant Dentistry and Related Research, Implant Dentistry, and Journal of Oral Implantology from 2005 to 2009 were reviewed. Nonoriginal articles were excluded. For each article included, extramural funding source, geographic origin, and study type were recorded. Descriptive and analytic analyses (α =.05), including a logistic regression analysis, and chi-square test were used where appropriate. Results: Of a total of 2,085 articles published, 1,503 met the inclusion criteria. The most common source of funding was from industry (32.4%). The proportion of studies that reported funding increased significantly over time. Europe represented the highest percentage (55.8%) of published articles. Most of the articles reported on clinical studies (49.9%), followed by animal studies (25.9%). Articles from Asia and South America and animal and in vitro studies were significantly more likely to be funded. Conclusion: Almost half of the original dental implant articles were funded. The trend toward internationalization of authorship was evident. A strong association was observed between funding and geographic origin and between funding and study type. Most studies in North America and Europe were clinical studies and supported by industry, whereas a greater proportion of studies in Asia and South America were in vitro or animal studies funded through government resources. © 2012 by Quintessence Publishing Co Inc.
Keywords: Funding; Implant; Internationalization; Study type